Thar Avani: A novel variety of round shape bottle gourd - Yadav, Lalu Prasad; K, Gangadhara; Apparao, V V; Singh, A K; Samadiya, D K (Indian Horticulture, 2023)
Thar Avani was developed at ICAR-Central Horticultural Experiment Station (CIAHRS), Godhra, Gujarat through hybridization followed by selection. The fruits are round in shape with 22.8 cm length, 39.4 cm girth, 8.1-8.7° TSS, 21.6 mg/100g ascorbic acid and 12.91 kg fruit weight. It has comparatively higher antioxidant contents and activity in fruit, epicarp, mesocarp and leaves. It also recorded comparatively higher potassium (1641.14), magnesium (155.36), iron (12.42) and copper (0.24) in fruit, and calcium (610.73), magnesium (158.17), iron (1.86), and copper (0.29) in leaves (mg/100 g dw).